Cytokine gene polymorphisms influence mucosal cytokine expression, gastric inflammation, and host specific colonisation during Helicobacter pylori infection. Issue 8 (9th July 2004) - Rad, R; Dossumbekova, A; Neu, B; Lang, R; Bauer, S; Saur, D; Gerhard, M; Prinz, C
Abstract : Background and aims: Recent studies linked cytokine gene polymorphisms to H pylori related gastric cancer development. The current study evaluated the role of cytokine gene polymorphisms for mucosal cytokine expression, the gastric inflammatory response, and bacterial colonisation during H pylori infection. Patients and methods: In 207 H pylori infected patients with chronic gastritis, polymorphisms at different loci of the interleukin ( IL ) -10, IL-1B, IL-1 receptor antagonist ( IL-1RN ), tumour necrosis factor (TNF)-A, and interferon (IFN)-G genes were genotyped by polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP) analysis, and allelic discriminating TaqMan PCR. Mucosal cytokine mRNA copy numbers were determined by real time quantitative PCR. Presence of bacterial virulence factors was investigated by cagA, vacAs1/2, and babA2 PCR. Biopsies were assessed with regard to the degrees of granulocytic/lymphocytic infiltration and the presence of intestinal metaplasia (IM) and atrophic gastritis (AG). Results: Proinflammatory IL-1 polymorphisms ( IL-1RN*2 + /IL-1B−511T/−31C + ) were associated with increased IL-1β expression, more severe degrees of inflammation, and an increased prevalence of IM and AG. Carriers of the IL-10−1082G/−819C/−592C alleles (GCC haplotype) had higher mucosal IL-10 mRNA levels than ATA haplotype carriers and were associated with colonisation by more virulent cagA +, vacAs1 +, and babA2 + H pylori strains. The TNF-A−307(G/A) and IFN-G+874(A/T) polymorphisms did not influence mucosal cytokine expression or the inflammatory response to H pylori . Conclusions: Cytokine gene polymorphisms influence mucosal cytokine expression, gastric inflammation, and the long term development of precancerous lesions in H pylori infection. Host polymorphisms are associated with certain bacterial strain types, suggesting host specific colonisation or adaptation. These findings contribute to the understanding of the complex interplay between host and bacterial factors involved in the development of gastric pathology.